Acupuncture. ISS 2022 guidelines for low back pain and migraine prophylaxis - Marianna Dara (Publiediting, 2022)
The popularity and interest in complementary therapies have significantly increased over the last century. Acupuncture is one of the therapies that has received the most attention. It can be considered the most important and certainly the most widespread part of traditional Chinese medicine. Practiced in China and neighboring regions for more than 3000 years as a prevention and treatment of various diseases, it spread to Europe and America from the sixteenth to the nineteenth century. In Italy, only in 2022 it became part of the guidelines recognized by the Istituto Superiore di Sanità for the treatment of chronic low back pain and migraine prophylaxis. This recognition makes acupuncture extremely topical in clinical practice.